2014
DOI: 10.1002/tox.21985
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on antioxidant status combined with integrated biomarker response inCarassius auratusfish exposed to nine phthalates

Abstract: Laboratory experiments were performed to determine the antioxidant responses to nine phthalates (PAEs) in the liver of the goldfish Carassius auratus. The fish were injected with 10 mg/kg body weight of each PAE for 1 day and 4, 8, and 15 days. The potential biotoxicity of the PAEs were examined using the antioxidase and lipid peroxide indices. We determined that the superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and malondialdehyde (MDA) levels displayed different trends following p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…The uses of phthalates as plasticizers are widely spread and growing rapidly in the manufacture of various PVC products, textiles, toys as well as medicinal products [1][2][3][4]. Moreover, they can be applied in various industries such as insect repellents, propellants and many cosmetics manufacture [3,4]. Due to its low cost production and its versatile chemical properties, phthalates attracted innumerable industrialists towards plastic-based productions throughout the world [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uses of phthalates as plasticizers are widely spread and growing rapidly in the manufacture of various PVC products, textiles, toys as well as medicinal products [1][2][3][4]. Moreover, they can be applied in various industries such as insect repellents, propellants and many cosmetics manufacture [3,4]. Due to its low cost production and its versatile chemical properties, phthalates attracted innumerable industrialists towards plastic-based productions throughout the world [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low cost production and its versatile chemical properties, phthalates attracted innumerable industrialists towards plastic-based productions throughout the world [3,5]. Being widely used as plasticizers and not bounded to polymer mesh, they easily pass from plastic products to surrounding environments and consequently pollute water, soil, air and last but not least food products [4,[6][7][8][9]. Rainfall transfers phthalates and phthalate esters in the atmosphere, which lead to their accumulation in water depending on geographic locations [8].…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2013), which scatter the potential risk for human exposure (Romani et al, 2014). Moreover, PAEs are considered to be a class of environmental endocrine disruptors which could cause testicular effect, influence the hormone synthesis and increase miscarriages or other gestational complications (Qu et al, 2009;Hansen and Grafton, 1994;Suzuki et al, 2001). To investigate the interaction between HSA and PAEs in detail has significant meaning for further understanding the pharma-cokinetics and pharmacodynamic properties of PAEs as it strongly affect the distribution of PAEs and the free fraction that is available for subsequent interactions with targeted receptors.…”
Section: Introductionmentioning
confidence: 99%
“…DBP; Weir, Wooten, Smith & Salice 2014), that may affect thyroid function (Mathieu-Denoncourt et al, 2015), neurodevelopment, reduced steroidogenesis, genotoxic and antioxidant status effects (Qu, Feng, Sun & Wang 2014;Wang, Jiang, Ge, Chen, Yang, Ji, Zhong, Guan & Liu 2015), autism spectrum disorders, and development/ reproductive physiology in animals (Aoki, Harris, Katsiadaki & Sumpter 2011;Bello, Madekurozwa, Groenewald, Aire & Arukwe 2014;Bhatia, Kumar, Ogino, Gregg, Chapman, McLaughlin & Iguchi 2014;Chopra, Harley, Lahiff & Eskenazi 2014); furthermore, they are thought to be carcinogenic (Ahuactzin-Perez, Torres, Rodriguez-Pastrana, Soriano-Santos, Diaz-Godinez, Diaz, Tlecuitl-Beristain & Sanchez 2014). DBP; Weir, Wooten, Smith & Salice 2014), that may affect thyroid function (Mathieu-Denoncourt et al, 2015), neurodevelopment, reduced steroidogenesis, genotoxic and antioxidant status effects (Qu, Feng, Sun & Wang 2014;Wang, Jiang, Ge, Chen, Yang, Ji, Zhong, Guan & Liu 2015), autism spectrum disorders, and development/ reproductive physiology in animals (Aoki, Harris, Katsiadaki & Sumpter 2011;Bello, Madekurozwa, Groenewald, Aire & Arukwe 2014;Bhatia, Kumar, Ogino, Gregg, Chapman, McLaughlin & Iguchi 2014;Chopra, Harley, Lahiff & Eskenazi 2014); furthermore, they are thought to be carcinogenic (Ahuactzin-Perez, Torres, Rodriguez-Pastrana, Soriano-Santos, Diaz-Godinez, Diaz, Tlecuitl-Beristain & Sanchez 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, DBP mode of action is unclear; independent studies have shown phthalates to be endocrine disruptors (4-6 carbon straight side chain compunds, i.e. DBP; Weir, Wooten, Smith & Salice 2014), that may affect thyroid function (Mathieu-Denoncourt et al, 2015), neurodevelopment, reduced steroidogenesis, genotoxic and antioxidant status effects (Qu, Feng, Sun & Wang 2014;Wang, Jiang, Ge, Chen, Yang, Ji, Zhong, Guan & Liu 2015), autism spectrum disorders, and development/ reproductive physiology in animals (Aoki, Harris, Katsiadaki & Sumpter 2011;Bello, Madekurozwa, Groenewald, Aire & Arukwe 2014;Bhatia, Kumar, Ogino, Gregg, Chapman, McLaughlin & Iguchi 2014;Chopra, Harley, Lahiff & Eskenazi 2014); furthermore, they are thought to be carcinogenic (Ahuactzin-Perez, Torres, Rodriguez-Pastrana, Soriano-Santos, Diaz-Godinez, Diaz, Tlecuitl-Beristain & Sanchez 2014). Antiandrogenic activity have been shown in adult male three-spined sticklebacks (Gasterosteus aculetaus) exposed to 15, and 35 mg DBP L À1 for 22 days by Aoki et al (2011); however it is unclear if they have any oestrogenic induction effect in fish (Ortiz-Zarragoitia, Trant & Cajaravillet 2006;Bhatia et al 2014;Chen, Li, Liu & Xu 2015).…”
Section: Introductionmentioning
confidence: 99%